Perlindungan Hukum Bagi Para Pihak Akibat Perbuatan Tindak Pidana Yang dilakukan Oleh Notaris - Gassanova Farah Diba; Wira Franciska; Felicitas Sri Marniati (JOURNAL of LEGAL RESEARCH, 2022)
The involvement of a notary in a criminal case is caused by the negligence and carelessness of the notary. Such as the criminal act of falsifying the deed he made intentionally. As in several cases examined in this study. The type of research used in this research is normative juridical. The research approach used is a statutory approach, an analytical approach and a case approach. The results of the research obtained are the legal consequences of a Notary deed containing elements of forgery does not automatically result in the deed being null and void, because the aggrieved parties must file a civil lawsuit to the court to cancel the deed. If a court decision has permanent legal force, then the deed can be annulled. Notaries cannot be held criminally responsible for deed falsification if it is not proven that there was an intentional factor, because the Notary only records what was submitted by the parties to be included in the deed. False information submitted by the parties is the responsibility of the parties. However, if it is proven that there is an element of intent, the notary can be held criminally responsible.